Some Properties of (𝑟,𝑠)-𝑇0 and (𝑟,𝑠)-𝑇1 Spaces - S. E. Abbas; Biljana Krsteska (International Journal of Mathematics and Mathematical Sciences)
We define (𝑟,𝑠)-quasi-𝑇0, (𝑟,𝑠)-sub-𝑇0, (𝑟,𝑠)-𝑇0 and (𝑟,𝑠)-𝑇1 spaces in an intuitionistic fuzzy topological space and investigate some properties of these spaces and the relationships between them. Moreover, we study properties of subspaces and their products.